Rational Construction of Nano-Scaled FeOOH/NiFe-LDH for Efficient Water Splitting - Juan Yu; Xiubing Fu; Haoqi Wang; Shun Lu; Bing Li (Nanomaterials)
In this paper, we use the facile approach for preparing novel, low-cost, efficient electrocatalysts for electrocatalytic water splitting. Interfacial engineering can significantly enhance the intrinsic performance of electrocatalysts. Herein, self-supporting FeOOH/NiFe-layered double hydroxide (LDH) nanosheet arrays were synthesized via hydrothermal and impregnation methods. The resulting FeOOH/NiFe-LDH can provide more active regions, which provide more active regions for co-reaction to proceed and accelerates electron transmit processes. Additionally, the amorphous FeOOH provides abundant active sites with low coordination, leading to excellent activity. The FeOOH/NiFe-LDH demonstrates remarkable two half-reaction electrocatalytic activity, along with excellent overpotentials of 168 mV (OER) and 155 mV (HER). This research introduces a sophisticated and scalable methodology for the creation of remarkably efficient and resilient alkaline conditions specifically designed for the HER and OER.